Geoengineering and the politics of science. (May 2014) - Hamilton, Clive
The latest reports from the Intergovernmental Panel on Climate Change (IPCC) include an assessment of geoengineering—methods for removing carbon dioxide from the atmosphere, or cooling the Earth by reflecting more of the sun's radiation back into space. The IPCC assessment signals the arrival of geoengineering into the mainstream of climate science, and may normalize climate engineering as a policy response to global warming. Already, conservative forces in the United States are promoting it as a substitute for emissions reductions. Climate scientists are sharply divided over geoengineering, in much the same way that Manhattan Project scientists were divided over nuclear weapons after World War II. Testing a geoengineering scheme, such as sulfate aerosol spraying, is inherently difficult. Deployment would make political decision makers highly dependent on a technocratic elite. In a geoengineered world, experts would control the conditions of daily life, and it is unlikely that such a regime would be a just one. A disproportionate number of scientists currently working on geoengineering have either worked at, or collaborated with, the Lawrence Livermore National Laboratory. The history of US nuclear weapons laboratories during the Cold War reveals a belief in humankind's right to exercise total mastery over nature. With geoengineering, this kind of thinking is staging a powerful comeback in the face of climate crisis.